A preliminary design of janazah washing area: upholding human dignity in the last rite-diversity among different - Zainal Abidin, Nabilah; Akasah, Zainal Abidin Akasah; Husin, Muhammad Riduwan (2013)
This paper will discuss on literatures and the problems that occur to Muslim community that are dealing with the activity of washing a janazah. The objectives of this study are to perform the final religious obligation of burial, which includes washing the body, shrouding, and performing janazah prayers for a deceased Muslim and to create awareness of the Muslim community and other believers towards the importance of the duty towards a deceased Muslim and respect towards the deceased. Last but not least to upholding human dignity in the last rite and diversity among different believers. This research has been written based on library search, internet retrieval, questionnaires in order to get the information regarding to the activity. Analyses of interviews are also conducted to help in organising the research. As a result it is to conclude that by implementing a new design of wash area, it would help increase the awareness towards a deceased Muslim and respect towards the deceased in the modern Islamic community.